IMPLEMENTATION OF ORTIZ CAKE AND BAKERY BUSINESS MARKETING STRATEGY IN BRUMBUNG - DEMAK - Nining Hidayah; Dina Kharisma (SEAN Institute, 2022)
Ortiz cake bakery is a business that sells various types of bread, brownies, cakes, pudding, and snack snacks with raw materials that are guaranteed quality. With the application of marketing strategies also aimed at balancing theory and practice in learning in the context of broader benefits, marketing strategy training in this business is expected to increase the number of orders/sales to increase economic growth. It can further reduce the level of educated unemployment. However, in terms of sales or marketing it is necessary to carry out training activities on the implementation of marketing strategies in the company Cake And Backery Ortiz to increase intensive outlets to create orders that increase or increase the number of sales and can have a profitable prospect in the future, and The more workers, the greater the employment created. This study aims to implement a cake and bakery business marketing strategy. The method used to overcome the problems faced by partners is to carry out training activities on implementing marketing strategies. Data collection methods This study was conducted using descriptive analysis, interview data collection techniques, making observations, and sampling techniques .sample in this study is management Ortiz cake and Bakery. The implementation of the messaging strategy is carried out using online media and brochures, as well as celebgram endorsements and implemented marketing strategies for the price, product, promotion, and place.,